2019
DOI: 10.3389/fpubh.2019.00254
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of the Implementation of Guidelines for Healthier Canteens in Dutch Secondary Schools: Study Protocol of a Quasi-Experimental Trial

Abstract: Introduction: To encourage healthier food/drink choices, the “Guidelines for Healthier Canteens” were developed by the Netherlands Nutrition Centre. This paper describes (1) how we developed a plan to support implementation of the “Guidelines for Healthier Canteens” in Dutch secondary schools, and (2) how we will evaluate this plan on process and effect level.Materials and Methods: The implementation plan (consisting of several tools) was developed in cooperation with stakeholders. Barriers/facilitators to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Therefore, it is important to (1) describe the core intervention functions of each tool of the implementation plan to be able to support schools with the same support and (2) to measure if the tools has been delivered and used as planned [12,56,57]. In our case, the core elements of the intervention have been described in the study design [34]. In addition to the effect evaluation, we also evaluated the quality of implementation to assess whether schools received each implementation tool [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to (1) describe the core intervention functions of each tool of the implementation plan to be able to support schools with the same support and (2) to measure if the tools has been delivered and used as planned [12,56,57]. In our case, the core elements of the intervention have been described in the study design [34]. In addition to the effect evaluation, we also evaluated the quality of implementation to assess whether schools received each implementation tool [38].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on the outcome purchase behaviour, an expected 10% drop out, 80% power and 5% significance level [34]. The calculation showed that 20 schools and 100 students per school were necessary to be able to detect a 10% difference in purchase behaviour of students (continuous variable), with the expected multi-level structure (students within schools, intra-class correlation of 0.05).…”
Section: Sample Sizementioning
confidence: 99%
“…This calculation was based on the effect outcome: students’ purchase behaviour, with a multi-level structure of students within schools (with a correlation of 0.05 between schools), an expected 10% drop-out, 80% power, and 5% significance level. Detailed information about the study design, intervention, and effect evaluation has been described previously [13]. The study protocol was approved by the Medical Ethical Committee of the VU University Amsterdam (Nr.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 summarizes each intervention tool. A more detailed explanation is available separately [13]. The tools were offered by a school canteen advisor of the Netherlands Nutrition Centre, in collaboration with the Vrije Universiteit Amsterdam.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation